Formulation of a new filter aids material for fabric filtration system - Abd. Rahim, Siti Hajar (2015)
A fabric filtration system has an advantage of a very high collection efficiency of more than ninety nine percent. However, the problem associated with fabric filter is that it has a short life span due to wear and tear connected with the operating conditions of the system. Treatment of fabric filter using pre-coating material is one of the simplest techniques to overcome this problem. The material works as a filter aids that will coat a layer of inert material onto the surface of the fabric and simultaneously acts as a filter cake barrier allowing a uniform airflow passing through the filter media. Thus, the study is to investigate and evaluate the characteristics and performance of a newly formulated filter aids designated as PrekotAC (a combination of filter aids material, PreKot™ and activated carbon) that will work as two in one material i.e. an adsorbent and a pre-coating material for a fabric filtration system. The PreKot™ and activated carbon were mixed in four different weight combinations of 10:90, 20:80, 30:70 and 40:60. Each material was tested on its physical characteristics, pressure drop, air permeability and particle penetration properties across a polytetrafluoroethylene (PTFE) filter media. It was found that the application of PrekotAC as a filter aids in the filtration system helped to reduce the pressure drop across the filter cake as well as increased the collection efficiency of fine particles compared to the performance of PTFE filter media alone. The results showed that PrekotAC possesses the suitable characteristics as a filter aids and flue gas cleaning agent, with low pressure drop, high air permeability and low particle penetration across the filter media in comparison of using activated carbon alone.